Birds of an Iowa dooryard - Sherman, Althea R. (Althea Rosina), 1853-1943 (Bur oak book., 1996)
Now available in paperback with a new foreword by Marcia Myers Bonta, Birds of an Iowa Dooryard contains Althea Sherman's often caustic, always careful studies of the phoebes, wrens, cuckoos, rails, catbirds, owls, flickers, and many other species that inhabited her Acre of Birds in northern Iowa. Birds of an Iowa Dooryard, first published in 1952, is full of Sherman's meticulous observations of species both avian and human. Her paintings, her notebooks and publications, and her innovative chimney swift tower form a remarkably rich legacy to be valued by naturalists and researchers alike.